2009
DOI: 10.1007/s00128-009-9759-8
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Growth, and Body Residues of Hyalella azteca (Saussure) Exposed to Fipronil Contaminated Sediments from Non-Vegetated and Vegetated Microcosms

Abstract: We assessed chronic effects of fipronil and metabolite contaminated sediments from non-vegetated and Thallia dealbata vegetated wetland microcosms on Hyalella azteca during wet and dry exposures. Mean sediment concentrations (ng g -1 ) ranged from 0.72-1.26, 0.01-0.69, 0.07-0.23, and 0.49-7.87 for fipronil, fipronilsulfide, fipronil-sulfone, and fipronil-desulfinyl, respectively. No significant differences in animal survival or growth were observed between non-vegetated and vegetated microcosms during wet or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Crustaceans are capable of accumulating high concentrations of fipronil, suggesting that tolerance is due to ability to detoxify or immunity to the effects of the chemical (Gunasekara et al, 2007). Similar to our observation that fipronil desulfinyl was accumulating in the eggs of wild C. sapidus females at low ng/g concentrations, Kröger et al (2009) found that fipronil was capable of accumulating in lipid and muscle tissue of P. clarkia and H. azteca at concentrations ranging from 1 to 5 ng/g.…”
Section: Discussionsupporting
confidence: 87%
“…Crustaceans are capable of accumulating high concentrations of fipronil, suggesting that tolerance is due to ability to detoxify or immunity to the effects of the chemical (Gunasekara et al, 2007). Similar to our observation that fipronil desulfinyl was accumulating in the eggs of wild C. sapidus females at low ng/g concentrations, Kröger et al (2009) found that fipronil was capable of accumulating in lipid and muscle tissue of P. clarkia and H. azteca at concentrations ranging from 1 to 5 ng/g.…”
Section: Discussionsupporting
confidence: 87%
“…The detection of DDT and its metabolites was unexpected, because this pesticide has been banned in the United States since 1972. Detected concentrations of individual insecticides are, however, far below reported 96‐h or 10‐d LC50 values for our test species 33–36, and no effect on H. azteca survival or growth was observed in 28‐d exposures to sediments containing more than 70 ng/g fipronil sulfone 37. Little is known about the species‐specific effects of complex chemical mixtures, and the discussion of potential effects on our test organisms therefore remains speculative.…”
Section: Discussionmentioning
confidence: 59%
“…Several studies have assessed effects of a single pesticide on sediment-associated aquatic animals in wetlands designed to mitigate agricultural runoff (Milam et al 2005;Bouldin et al 2007;Kröger et al 2009). Few studies, however, included assessments of pesticide mixtures in wetlands designed to mitigate agricultural runoff Moore et al 2007).…”
Section: Discussionmentioning
confidence: 99%